INTERNET AND SOCIAL MEDIA CHANGE: UTILIZATION OF SOCIAL MEDIA FOR LITERACY AND ADVOCACY IN DRONE EMPRIT /MEDIA KERNELS: (Case Study of Fuel Price Increase) - Pangestu, Bernavita Fiana; Perlita, Janet (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Currently, information and communication technology that is networked with the internet continues to grow rapidly, with the internet providing public information disclosure that seems to have no distance between individuals. The existence of technology has affected media consumption both directly and indirectly, so success in building digital literacy is an indication of modernization amid public consumption. Changes in digital media consumers are also influenced by reader behavior, so it is important to improve digital skills and literacy amid the development of technology and information. One of the efforts is to support the use of Drone Emprit with expertise in Artificial Intelligence (AI) and Natural Learning Process (NLP) through Media Kernels software developed by local children. Currently, Indonesian society is entering the era of industrial revolution 4.0 with the dissemination of information to the public in a modern digital society where online media or mass media plays an important role in social media because it is interconnected and interacts with each other among users. Media. The research method used uses a qualitative method with a descriptive approach through interviews with 2 (two) sources that match the experts. The results showed that the strategic role of social media in this digitalization era is influenced by the formation of public opinion, and current technology has also taken root in people's lives. So, with the help of the internet, spatial limitations can still be overcome including 3T areas (underdeveloped, frontier, outermost).